Combined with fractional condensation to upgrade the liquid products derived from the co-pyrolysis of bio-oil distillation residue and bituminous coal. (1st April 2019) - Zhu, Xiefei; Li, Shiying; Luo, Zejun; Zhu, Xifeng
Highlights: High percentage of distillation residue contributed to all graded bio-oil yields. Linear model was recommended for the prediction of the graded bio-oil yield. Blending bituminous coal could disturb the distribution of bio-oil compounds. The products from distillation residue were more abundant than bituminous coal. Abstract: In this study, the effects of induction conditions on the distribution characteristics of graded bio-oil derived from the co-pyrolysis of bio-oil distillation residue and bituminous coal were investigated in a fixed pyrolysis reactor with a three-stage condenser. Based on the central composite design and statistical analysis, it could be found that a quadratic model was recommended to depict the total bio-oil yield, whereas the linear model was the best-fitting model for the graded bio-oil yield of different condensation stages. As for total bio-oil yield, all the combined effects of induction conditions played a negative role, and all second-order effects were advantageous. Moreover, the high percentage of distillation residue contributed to the bio-oil yield at each condenser and had the greatest impact on the bio-oil yield of the first condenser. However, high temperatures and high gas flow rates reduced the bio-oil yield of the first condenser and favored the increase in bio-oil yield of subsequent condensers. In addition, the products derived from distillation residue were more abundant than bituminous coal. And the addition of bituminous coal did not significantly increase the type of compounds in bio-oil from the blends, but disturbed the distribution of bio-oil products. The condensers with different temperatures facilitated the separation and enrichment of different compounds.